(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to explore the role of training programs in enhancing job performance among employees of Jumhouria Bank, South Tripoli Branch. A sample of 30 employees was randomly selected from the bank. A questionnaire consisting of 16 items, based on a five-point Likert scale, was used to measure the impact of training programs on employees’ skills, competence, motivation, and overall job performance. The findings revealed that the majority of employees believed that training programs contributed to the development of their professional skills and improved the quality of their job performance. Many respondents also indicated that training increased their self-confidence and helped them adapt to organizational and technological changes in the workplace. Furthermore, a clear positive effect of training programs on employee motivation and commitment to performing their tasks more effectively was observed. Although some respondents expressed reservations or neutrality regarding the effectiveness of training in certain aspects, the overall results support the hypothesis of a statistically significant positive relationship between training programs and job performance. Participants also emphasized the importance of continuous training and the role of the organization in updating training programs based on trainees’ feedback. The study recommends the continuous development of training programs, with a focus on incorporating interactive training methods and creating a motivating environment to meet diverse employee needs. It also highlights the importance of investing in training as a strategic approach to building strong human capital that contributes to achieving organizational goals and enhancing performance efficiency in a sustainable manner.